This study aims to test and find out (1) the effect of leadership style on teacher work motivation, (2) the effect of the work environment on teacher work motivation, (3) the effect of leadership style on teacher performance, (4) the effect of work environment on teacher performance (5) the effect of motivation work on teacher performance. This study uses a quantitative approach using path analysis through SPSS statistical analysis software. Leadership style positively affects motivation, with  - Hanifah Noviandari; Diningrum Citraningsih; Kharis Syuhud Mujahada (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2022)
This study aims to test and find out (1) the effect of leadership style on teacher work motivation, (2) the effect of the work environment on teacher work motivation, (3) the effect of leadership style on teacher performance, (4) the effect of work environment on teacher performance (5) the effect of motivation work on teacher performance. This study uses a quantitative approach using path analysis through SPSS statistical analysis software. Leadership style positively affects motivation, with a significance value of 0.770, greater than a significance = 0.05, and a beta coefficient of 0.027. The environment has a positive and significant effect on teacher performance with a significance value of 0.000 which is less than the value a = 0.05, and the beta coefficient shows 0.871. Motivation has no significant positive effect on teacher performance, with a significance value of 0.401, less than a = 0.05, and the beta coefficient shows the number 0.200. From these results, leadership and work environment will affect motivation and will have an impact on performance. In other words, leadership and work environment, directly and indirectly, affect performance through motivation.